From Abstract Form to Concrete Materialization: An Analysis of Mazu’s Image in Statues and Images - Beibei Zhang; Xiaping Shu (Religions, 2022)
The religious color of folk beliefs and customs, a concrete and ideal artistic presentation of the Mazu (媽祖) image reflected in ancient books, folk customs and myths, endows Mazu with its unique image and humanistic connotation. The visual image, which implies the meaning of the thought, serves as important material for historical research. Therefore, this paper refers to and draws on three changing images of Mazu summarized from the perspectives of state and society, social function, and region of belief, respectively, by anthropological researcher Mr. Bozhong Li in his study of Mazu. Based on the analysis of Mazu image data, three significant images of Mazu are proposed, namely, the initial image, the transformation image and the typical image, along with a comprehensive analysis of its evolution and relationship. The image of Mazu in the statue is not only an artificially constructed social and cultural symbol but also a folk art symbol with religious and folk characteristics, and secular and emotional characteristics. It is also the visual form of Mazu’s intuitive concrete materialization, carrying a certain representative thought and concept, meaning and spirit, and the various pieces of information it contains is more intuitive than words, bringing the incomparable dissemination power of knowledge and information from the classics. Moreover, it can transcend language barriers and regional boundaries, stimulate personal inner original feelings, interact with Mazu’s beliefs and customs, and serve as an important medium for spreading Mazu’s beliefs and customs.